Regional Autonomy in the Context of Regional Regulations - Yofi Permatasari; Andika Jinaratana; Criestian Hadiwinata; Pascal Amadeo Yapputro; Maulida Syahrin Najmi (Pelopor Publikasi Akademika, 2023)
This study discusses local autonomy in the context of local regulation. Based on the 2014 Law No. 23 on Local Governments, Article 1, Paragraph 6, local governments are defined as the execution of administrative affairs by local governments based on the principle of local autonomy. Regional autonomy is the right, authority and duty of autonomous regions to regulate and control their own government affairs and the interests of their communities within the unitary national system of the Republic of Indonesia. Regional chiefs are empowered to organize and control the affairs of their regional governments, but must still take precedence over national law. One way to promote local autonomy in governance is to require a system that can implement democratic principles that provide opportunities for citizens to participate in state government. This discussion describes how the role of local regulation has emerged and how it affects central governments in maintaining local autonomy practices.